Synthesis and Anticancer Activity of 1-(1H-Indol-3-yl)-2-(4-diarylmethylpiperazine-1-yl)ethane-1,2-dione Derivatives - Jun-Rong Jiang; Feng Xu; Han-Gui Wu (Journal of Chemistry)
Several new 1-(4-diarylmethylpiperazine-1-yl)-2-(1H-indol-3-yl)ethane-1,2-dione derivatives were synthesized by acylation of 1-diarylmethylpiperazine with 2-(1H-indol-3-yl)-2-oxoacetyl chloride. Their structures were confirmed by 1H NMR, IR, mass spectra, and elemental analysis. These compounds were further evaluated for their anticancer activity, and most of them were found to have moderate-to-potent antiproliferative activities against Hela, A-549, and ECA-109 cancer cell lines in vitro.